Malawi : Technical Assistance Report on the Price Statistics Mission. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2013)
This paper discusses the findings of a Technical Assistance Report on the Price Statistics Mission to Malawi. It was concluded that more than 80 percent of the country unit values selected as the price indicators for the macroprudential indicators did not provide credible indicators of pure price change over time. The compilation of the indexes could therefore not be undertaken until import and export price surveys had been initiated. Plans were developed for the conduct of an intensive program of field interviews to initialize the quarterly price collections. Training was provided on index concepts, compilation methodology, and price survey design and implementation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet